Microwave activation of electrochemical processes: enhanced electrodehalogenation in organic solvent media. - Tsai, Y; Coles, B; Compton, R; Marken, F (2002)
The effect of high-intensity microwave radiation focused into a "hot spot" region in the vicinity of an electrode on electrochemical processes with and without coupled chemical reaction steps has been investigated in organic solvent media. First, the electrochemically reversible oxidation of ferrocene in acetonitrile and DMF is shown to be affected by microwave-induced thermal activation, resulting in increased currents and voltammetric wave shape effects. A FIDAP simulation investigation allows quantitative insight into the temperature distribution and concentration gradients at the electrode / solution interface. Next, the effect of intense microwave radiation on electroorganic reactions is considered for the case of ECE processes. Experimental data for the reduction of p-bromonitrobenzene, o-bromonitrobenzene, and m-iodonitrobenzene in DMF and acetonitrile are analyzed in terms of an electron transfer (E), followed by a chemical dehalogenation step (C), and finally followed by another electron-transfer step (E). The presence of the "hot spot" in the solution phase favors processes with high activation barriers.